Beyond style: character evolution through fashion illustration - Dahaman, Rizal Azni; Baharom, Mohd Khairi; Md Nor, Zainudin; Mustapha, Shahrizad Fitri (2024)
Discovering the theme of "Beyond Style: Character Evolution Through Fashion Illustration" involves fashion illustration that highlights individuality, diversity, the expressive nature of the art form and how it relates to fashion illustration. In the context of fashion illustration, this theme portrays the unique characteristics of the subjects, and the creations infuse with the identity and spirit. Fashion illustration becomes a testament to the belief that style is a deeply personal expression, and each stroke of the artist's brush is a verse to the multi-layered nature of humanity. It is an acknowledgment that beauty is not confined to a singular standard but is found in the myriad shapes, sizes, colours, and cultures that make up our diverse world. Fashion illustrators have embraced "character” more than artistic technique. It becomes a philosophy that challenges norms, redefines beauty standards, and appreciates the richness found in the authenticity of individual stories. The journey through the intricate lines and vibrant hues captures the style of character in fashion illustration. Character is not just a stylistic choice; it is a powerful assertion of thoughtful impact of personal expression within the art form.